A Unified framework for using micro-data to compare dynamic wage and price setting models - Huw David Dixon (Center for Economic Studies and ifo Institute (CESifo), 2010)
This paper develops a statistical framework of steady-state identities which enable us to match the distributions of durations found in the micro-data to generalized Taylor and Calvo models of time-dependent pricing. We illustrate the approach with the UK micro CPI data for 2006-2009, and employ the pricing models in a simple macromodel. We find that the Generalized Taylor Economy generates a hump shaped response function, whilst the Generalized Calvo does not.
Keywords: E50; 330; price-spell; steady state; hazard rate; Calvo; Taylor; Preisrigidität; Lohnrigidität; Stationäre Volkswirtschaft; Preistheorie; Mikrodaten; Theorie